Quality of life in primary headaches and biofeedback effects - N. L. Starikova (Бюллетень сибирской медицины)
Determinants of quality of life (QoL) in primary headaches remain unclear. We studied QoL in 107 patients (50 migraine patients, 57 tension-type headache — TTH-patients) and 10 healthy subjects. QoL in headache patients was reduced and strongly correlated with passive coping strategies preference, levels of anxiety and depression. In migraine QoL depended on duration of the disease, intensity of pain and MIDAS score. In TTH no clinical features of the disease influenced QoL. Biofeedback showed high effectiveness in primary headaches which depended on coping strategies of patients.